Knowledge about Rh-incompatibility and its associated factors among antenatal care recipients in public hospitals of Wolaita zone, 2022: facility-based cross-sectional study - Temesgen Geta; Bizuayehu Atinafu; Tsiyon Kassa (BMJ Publishing Group, 2024)
Background Lack of awareness about the Rh-incompatibility problem is one of the factors hindering early prevention in Ethiopia. Thus, the objective of this study is to determine what was known about Rh-incompatibility disorders and their associated factors among pregnant women participating in prenatal care in southern Ethiopia.Design, setting and participants A facility-based cross-sectional study was employed in four selected hospitals during 1-30 August 2022. The systematic random sampling method was used as a technique of selecting the study participants. The study was performed using a structured questionnaire. The data were coded and entered into EPI DATA V.4.6, and then the analysis was done using SPSS V.23 software program. Adjusted OR with 95% CI was the measurement unit of association between independent variables and outcome variables. The significance level was established as p<0.05.Result 414 women took the survey, which corresponds to a response rate of 98.1%. Of those who responded, only 48% knew their blood group. The study found that 35.3% (95% CI: 31% to 40%) of women had a good knowledge of Rh-incompatibility. Maternal educational level above secondary school, multigravida women, blood type screening in the maternity ward, early counselling on Rh status and Rh-incompatibility and a positive attitude among women were significantly associated with pregnant women's knowledge of Rh-incompatibility.Conclusion The majority of pregnant women had poor knowledge regarding Rh-incompatibility. Therefore, all responsible organisations should focus on expanding pregnant women's knowledge of Rh-incompatibility and the factors significantly associated with knowledge of Rh-incompatibility.